Penegakan Hukum terhadap Insider Trading di Pasar Modal dan Upaya Perlindungan terhadap Investor - Husnul Khowatim; Nurul Wasilatur Rofi’ah; Intan Permata Sari; Salman Farisi; Karisma Putri Noviana; Firza Agung Prakoso (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
The capital market plays a strategic role in supporting national economic growth through its function of raising funds and providing investment vehicles for the public. However, the integrity of the capital market is often threatened by the practice of insider trading, which involves securities transactions conducted using material, non-public information by certain parties for personal gain. This practice violates the principles of fairness and transparency and has the potential to harm public investors and undermine confidence in the capital market. This study aims to analyze the law enforcement mechanisms for insider trading in the Indonesian capital market and examine legal protection efforts for investors. The research method used is qualitative research with a descriptive approach through a literature review of laws and regulations, scientific journals, books, and publications from the Financial Services Authority (OJK) and the Indonesia Stock Exchange. The results indicate that law enforcement against insider trading is carried out through mechanisms of supervision, investigation, and the imposition of administrative, civil, and criminal sanctions. However, the effectiveness of law enforcement still faces various challenges, particularly in proving the use of insider information and the complexity of transaction technology. Furthermore, insider trading negatively impacts investor confidence and capital market stability. Investor protection efforts are implemented through a preventative approach, including information disclosure, supervision, and investor education, as well as a repressive approach through legal sanctions, dispute resolution, and whistleblower protection. This research is expected to provide theoretical contributions to the development of capital market law and practical recommendations for strengthening law enforcement and investor protection in Indonesia.